1994
DOI: 10.1152/ajpheart.1994.267.4.h1549
|View full text |Cite
|
Sign up to set email alerts
|

Role of rostral ventrolateral medulla in centrally mediated pressor responses

Abstract: The region of the rostral ventrolateral medulla (RVLM) plays an important role in central nervous system regulation of cardiovascular function. The initial purpose of these studies was to determine whether synaptic activation of excitatory amino acid (EAA) receptors in the RVLM might mediate central pressor responses. Blockade of EAA receptors in the RVLM with kynurenic acid abolished pressor responses evoked by stimulation of sciatic nerve afferents but had no effect on increases in arterial pressure produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 0 publications
7
75
1
Order By: Relevance
“…Effective antagonism of ionotropic glutamate receptors in the RVLM evoked comparable decreases in SNA, HR, and MAP in OZR and LZR, and this was observed even after the elimination of potentially altered endogenous GABAergic inputs to the RVLM. Unexpectedly, even LZR displayed significant reductions in SNA, HR, and MAP with antagonism of glutamate receptors in the RVLM, in contrast to previous reports of a lack of physiological effects in other normotensive strains (19,20,22). The responses to inhibition of glutamatergic inputs to the RVLM observed in LZR were not likely due to specific conditions of our experiments, because under the same conditions blockade of glutamate receptors in SpragueDawley rats did not alter SNA, HR, or MAP.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Effective antagonism of ionotropic glutamate receptors in the RVLM evoked comparable decreases in SNA, HR, and MAP in OZR and LZR, and this was observed even after the elimination of potentially altered endogenous GABAergic inputs to the RVLM. Unexpectedly, even LZR displayed significant reductions in SNA, HR, and MAP with antagonism of glutamate receptors in the RVLM, in contrast to previous reports of a lack of physiological effects in other normotensive strains (19,20,22). The responses to inhibition of glutamatergic inputs to the RVLM observed in LZR were not likely due to specific conditions of our experiments, because under the same conditions blockade of glutamate receptors in SpragueDawley rats did not alter SNA, HR, or MAP.…”
Section: Discussioncontrasting
confidence: 71%
“…To confirm the blockade of ionotropic glutamate receptors in RVLM, stimulation of the right sciatic nerve (10 s of 1-ms pulses at 20 Hz and 300 A) was performed. These stimulation parameters produce reliable rises in SNA and MAP that are eliminated or reversed after antagonism of ionotropic glutamate receptors in the RVLM (22). All rats included in the study showed the expected responses before brain stem microinjections and an absence of responses after microinjections of kynurenate into the RVLM (see Fig.…”
Section: Methodsmentioning
confidence: 89%
“…The pattern of cardiovascular adjustments observed in the present study is also compatible with previously described data (Kiely and Gordon 1994, Yardley and Hilton 1987, Hilton and Zbrozyna 1963. This pattern is characterized by increases in arterial blood pressure and heart rate.…”
Section: Nitric Oxide Release In Defense Reactionsupporting
confidence: 93%
“…18 As mentioned above, injection of muscimol into the ipsilateral RVLM attenuated the pressor and sympathoexcitatory response evoked from the PVN by approximately one half. The dose of muscimol injected (1 nmol) was 10 times greater than that which has previously been shown to result in a profound fall in arterial pressure when injected bilaterally into the RVLM, 9 indicating that it was sufficient to produce complete or nearly complete inhibition of RVLM neurons. Thus, the fact that the pressor and sympathoexcitatory response evoked from the PVN was reduced but not abolished after injection of muscimol into the ipsilateral RVLM supports the finding of Kiely and Gordon 9 that this response is mediated partly by a descending pathway that includes a synapse within the RVLM and partly by a separate descending pathway that is independent of the RVLM.…”
Section: Tagawa and Dampney Function Of At 1 Receptors On Rvlm Pressomentioning
confidence: 78%
“…6 Although glutamate receptors have been shown to mediate excitatory synaptic inputs to RVLM sympathoexcitatory neurons that are activated by stimulation of a variety of peripheral receptors and some supramedullary regions, 1,2,7,8 there is also evidence that excitatory inputs to these neurons activated by stimulation of certain hypothalamic regions (eg, the paraventricular nucleus [PVN] and perifornical area) are nonglutamatergic. 9 This raises the possibility that AT 1 receptors in the RVLM may mediate excitatory inputs to RVLM neurons originating from these hypothalamic regions. To test this hypothesis, in the present study, we have determined the effect of specific blockade of AT 1 receptors in the RVLM on the excitation of RVLM sympathoexcitatory neurons evoked by activation of the hypothalamic PVN.…”
mentioning
confidence: 99%